Does External Debt Contribute To Malaysia Economic Growth? - Daud, SNM; Ahmad, A; Azman-Saini, WNW (Routledge Journals, Taylor & Francis Ltd, 2024)
This paper analyzes the contribution of external debt to Malaysia's economic growth. To investigate whether the external debt has contributed to the economic growth in the long run, the growth model is tested by applying the Autoregressive Distributed Lag (ARDL) bound test. In addition, the existence of the threshold effect is examined to estimate the optimal level of external debt. The empirical results reveal that the accumulation of external debt is associated with an increase in Malaysia's economic growth up to an optimal level, and an additional increase of external indebtedness beyond the level has inversely contributed to the Malaysian economy.